Evolution of Sequence Stratigraphy and Paleogeography, Case Study: M2 Member of the Muara Enim Formation - Hibatullah, Kevin Nabil; Setiawan, Budhi; Rochmana, Yogie Zulkurnia; Wicaksono, M. Dwiki Satrio (Jambura Geoscience Review, 2024)
Sequence stratigraphy related to accommodation space as an area of potential sediment accumulation that is influenced by fluctuations in sea level and subsidence of the basin floor. Paleogeography, on the other hand, is the study of physical geographic features and their evolution throughout geological periods. The aim of this work is to shed light on the relationship between paleogeographic evolution and sequence stratigraphy, as well as coal accumulation in the South Sumatra Basin. The method used are geophysical logs and cores analysis to determine the system tracts, types of system tracts, and stratigraphic sequences, lithofacies and sedimentary facies analysis, paleogeographic analysis using modified single-factor and multi-factor and them mapped  using IDW as a geostatistical method. The results indicate that the study area comprises four system tracts, namely TST-1, HST-1, TST-2 and HST-2. In TST-1 and TST-2, the rate of peat formation is balanced with the rate of accommodation space formation, resulting in continuous and very thick coal accumulation. In HST-1 and HST-2, the rate of accommodation space formation exceeds the rate of peat formation, leading to continuous coal accumulation that is quite thick to very thick. Sequence 1 consists of lagoon and tidal/mouth/distal bar paleogeographic unit with  sand/shale ratio range 0.217 to 0.247. Sequence 2 consists of lagoon paleogeographic units with sand/shale ratio range 0.046 to 0.05.